The welfare impacts of changes in the Brazilian domestic work market - Edson Paulo Domingues; Kênia Barreiro de Souza (International Policy Centre for Inclusive Growth (IPC-IG), 2012)
[Introduction ...] In Brazil, growth in domestic workers' income has been above the average growth rate of the economy, while, at the same time, the number of hired workers has changed very little, indicating that demand has remained high enough that no jobs were lost in the labour market. In this sense, this study sought to estimate the impact of increased wages paid to domestic workers, through simulations with a computable general equilibrium (CGE) model. As such, one can observe the implications of recent increases in the relative wages of domestic workers in Brazil, considering two concurrent effects: i) the increase in the price of domestic work; and ii) the income gains of domestic workers. Thus, one can assess not only the immediate results on the demand for domestic services but also the effects triggered elsewhere in the economy. Hence, the results indirectly show the likely consequences of formalisation and the inclusion of domestic work under the aegis of labour rights. According to the simulations presented in this study, this would lead to increased income for a portion of the population, and higher costs attached to these services.
Keywords: 330; Hauspersonal; Lohn; Brasilien